2022
DOI: 10.3390/nu14112202
|View full text |Cite
|
Sign up to set email alerts
|

Time-Related Eating Patterns Are Associated with the Total Daily Intake of Calories and Macronutrients in Day and Night Shift Workers

Abstract: The aim of the study was to investigate whether time-related eating patterns are associated with the daily intake of calories and macronutrients in Brazilian male military police officers (n = 81; 29-day and 52-night workers; mean age: 36.4 ± 0.9 and 38.5 ± 0.7 years, respectively). Energy and macronutrient intake were determined by a non-consecutive 3-day food recall. Time-related eating patterns, such as the time of the first and the last meals, eating duration, and caloric midpoint, were evaluated. Individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
(89 reference statements)
1
6
0
Order By: Relevance
“…Across shifts, the eating window is aligned with the waking time; the longer the waking time, the longer the eating window and the greater the calorie consumption [11]. The amount of energy intake seems to be associated with the eating window, as we showed in previous studies conducted from our research group [11,23]. Studying rotating shift workers from a miner company, we found that the wakefulness promoted by the transition from afternoon to night shifts leads to the largest eating window of the schedule (20.7 ± 1.2 h) and, consequently, the highest energy intake (3410 ± 235 kcal) at the same period [11].…”
Section: What Is the Main Problem Of Shift Workers Eating Habits: "Wh...supporting
confidence: 60%
See 3 more Smart Citations
“…Across shifts, the eating window is aligned with the waking time; the longer the waking time, the longer the eating window and the greater the calorie consumption [11]. The amount of energy intake seems to be associated with the eating window, as we showed in previous studies conducted from our research group [11,23]. Studying rotating shift workers from a miner company, we found that the wakefulness promoted by the transition from afternoon to night shifts leads to the largest eating window of the schedule (20.7 ± 1.2 h) and, consequently, the highest energy intake (3410 ± 235 kcal) at the same period [11].…”
Section: What Is the Main Problem Of Shift Workers Eating Habits: "Wh...supporting
confidence: 60%
“…In another study, we evaluated time-related eating patterns of day and night military police officers and showed that those shift workers with later caloric midpoint, both day and night shift workers, had higher energy intake compared to earlier eaters. However, when compared with day workers, night workers had a later caloric midpoint, which is a consequence of the extended period of wakefulness promoted by the night shift [23].…”
Section: What Is the Main Problem Of Shift Workers Eating Habits: "Wh...mentioning
confidence: 91%
See 2 more Smart Citations
“…Population studies suggest that late eating, which refers to a delay in the timing of meals (usually the main meal of the day or the last meal, i.e., dinner) [ 12 ] may be a factor implicated in obesity and other non-communicable diseases related to nutrition [ 13 , 14 , 15 ]. Potential mechanistic links through which meal timing may promote obesity and associated diseases include, among others, the lower diet quality and higher calorie intake observed in late eaters [ 16 , 17 , 18 ]. However, no prior studies to date have evaluated the possible association of meal timing with the intake of foods with different degrees of processing.…”
Section: Introductionmentioning
confidence: 99%